KRITIK TARIKH RUWAH DALAM STUDI HADIS - Wafa Amaliah (DIRAYAH : Jurnal Ilmu Hadis, 2025)
This study examines kritik tārīkh al-ruwāh (criticism of narrators’ historical biographies) as an integral part of hadith studies, particularly within the discipline of ʿilm al-rijāl. The research aims to analyze the concept, scope, urgency, and forms of scholarly criticism directed toward tārīkh al-ruwāh in the process of hadith authentication. This study employs a qualitative library research method by analyzing classical hadith sources, contemporary scholarly works, and relevant academic journal articles. The findings indicate that tārīkh al-ruwāh plays a crucial role in verifying the continuity of sanad, identifying the reliability of narrators, detecting cases of ikhtilāṭ, and distinguishing similar or overlapping narrator identities. Furthermore, scholarly criticism of tārīkh al-ruwāh mainly focuses on methodological differences, variations in historical data, and the structure of biographical compilations rather than rejecting its epistemological validity. This study concludes that tārīkh al-ruwāh remains an essential methodological instrument in hadith criticism and continues to be relevant for contemporary hadith scholarship when approached with a critical and systematic framework.